Resuscitation of very preterm infants with 30% vs. 50% oxygen: a randomized controlled trial - Risma Karina Kaban; Asril Aminullah; Rinawati Rohsiswatmo; Badriul Hegar; Abdurahman Sukadi; Peter Graham Davis (Indonesian Pediatric Society, 2022)
Background Preterm infants are susceptible to the damaging effects of hyperoxia which may lead to bronchopulmonary dysplasia (BPD) and intestinal damage. Hyperoxia also affects intestinal microbiota. The optimal initial FiO2 for the resuscitation of premature infants is unknown. Objective To determine the effect of different initial oxygen concentrations on BPD, oxidative stress markers, damage to the gastrointestinal mucosa, and the intestinal microbiome. Methods We conducted an unblinded, randomized controlled clinical trial in premature infants requiring supplemental oxygen in the first minutes of life. Infants started at an FiO2 of either 30% (low) or 50% (moderate), which was adjusted to achieve target oxygen saturations (SpO2) of 88-92% by 10 minutes of life using pulse oximetry. The primary outcome was incidence of BPD. Secondary outcomes included markers of oxidative stress [oxidized glutathione (GSH)/reduced glutathione (GSSG) ratio and malondialdehyde (MDA)], intestinal integrity indicated by fecal alpha-1 antitrypsin (AAT), and intestinal microbiota on fecal examination. Results Eighty-four infants were recruited. There was no significant difference in rates of BPD between the 30% FiO2 and 50% FiO2 groups (42.8% vs. 40.5%, respectively). Nor were there significant differences in GSH/GSSG ratios, MDA concentrations, fecal AAT levels, or changes in facultative anaerobic and anaerobic microbiota between groups. Conclusion In premature infants resuscitated using low vs. moderate initial FiO2 levels, we find no significant differences in BPD incidence, markers of oxidative stress, intestinal mucosa integrity, or intestinal microbiota.